KAJIAN PENGGUNAAN MEJA DAN KURSI ADJUSTABLE SMK NEGERI 3 MEDAN - Bayu, Bayu Herman Syah; Zaharuddin; Utama, Denny Walady (Jurnal Rekavasi, 2023)
The success of children in learning is strongly influenced by several factors such as the teacher, tools or facilities, facilities and infrastructure, the surrounding environment. One of the educational facilities and infrastructure that supports learning that is not given enough attention is the study desks and chairs for students in class. Tables and chairs are one of the most closely related factors in improving the quality of learning. If the tables and chairs are not ergonomic, during the learning process students will easily feel tired and not focus when learning takes place.This study aims to determine the factors that influence musculoskeletal complaints in students and find out whether adjustable tables and chairs can reduce these complaints. Completion in this study using anthropometric methods.The conclusion of this study is that there are several factors that cause musculoskeletal disorders, namely non-ergonomic seating, high chairs, high tables, inappropriate sitting positions, and sitting too bent. Where the results of the study stated that each table and chair size must be in accordance with its users, so that it can be used comfortably.   Keywords: adjustable tables and chairs, musculoskeletal, anthropometry.